Differential coastal uplift quantified by luminescence dating of marine terraces, central Cascadia forearc, Oregon. (15th December 2022) - McKenzie, K.A.; Kelsey, H.M.; Kirby, E.; Rittenour, T.M.; Furlong, K.P.
Abstract: Flights of marine terraces along the coastline of the Cascadia convergent margin record long-term, sustained crustal uplift of the subduction zone upper plate. At Yaquina Bay (Newport, Oregon) differences in the elevations of previously inferred MIS 5 (5a, 5c, and 5e) marine terraces north and south of the bay imply differences in the long-term uplift rate that are attributed to displacement along the Yaquina Bay fault – a west-to-east trending fault inferred to be located within the bay. Here we present the first direct ages for the marine terrace deposits at Yaquina Bay using luminescence dating of marine terrace sands on terrace treads to quantify long-term and interval uplift rates. These new age results in combination with high-resolution topographic data, allow us to refine previous mapping of marine terraces in the vicinity of Yaquina Bay, including the recognition of a MIS 5a terrace south of Yaquina Bay. Differences in the elevations of terraces north and south of Yaquina Bay confirm relative displacement along the Yaquina Bay fault since the late Pleistocene. Our results imply differences in the long-term uplift rate relative to sea level north and south of Yaquina Bay since ca. 125 ka; south of the fault, uplift rates appear to have been relatively constant at 0.3–0.4 m/kyr, whereas north of the fault, average uplift rates were greater, 0.7–0.9 m/kyr over the past ca. 125 kyrs. Notably, terrace elevations north of the fault require variations in uplift rate through time. Uplift rates appear to have been relatively low (≤0.1 m/kyr) between MIS 5e and 5c but increased to rates of ∼1.6 m/kyr in a ∼20 kyr period between MIS 5c and MIS 5a. Subsequently, uplift rates appear to have decreased to 0.7 m/kyr during the last ∼80 kyrs, but were sustained at rates approximately double that of the block south of the fault. These results require temporally variable slip along the Yaquina Bay fault since the late Pleistocene. Highlights: Surface classification of marine terraces using Lidar-derived elevation data. Luminescence dating of marine terrace deposits along the Cascadia margin. Vertical offset of MIS 5 marine terraces indicates subduction zone upper-plate faulting in coastal Oregon. Variable slip history on a subduction zone upper-plate fault from ca. 125 ka - present.